Enhancing Software Engineering Learning Environment with Computer Games: A Case Study - Rababaah, Aaron R. (Journal of Engineering Education Transformations, 2021)
Education gamification has been spreading in various disciplines such as languages, computer programming, medicine, natural languages, engineering, etc. Software Engineering is our interest in this work as we saw an opportunity of contribution to enrich literature and empirical studies in this area. Traditional methods of teaching Software Engineering could significantly benefit from gamification as a complementary component in student learning outcomes. We believe we can provide our students with more effective learning environment in number of aspects including: providing enjoyable practice, immediate feedback, enhancing the sense of responsibility, enhanced engagement and performance real time tracking. In this paper, we will present our case study in adopting a computer game in software engineering course. Further, we will present the results of a course exist survey that shows the responses of 114 participating students. The analysis of the survey showed significant positive impact on number of aspects including: student engagement, learning concepts and critical thinking. The overall mean of positive responses was 81.2%.